Imagined democracies : necessary political fictions - Ezrahi, Yaron (Cambridge University Press, 2012)
"In our era of mass electronic communications, political realities are produced by believable fictions that echo popular desires. Hence the pressing question facing contemporary democracies is how to privilege the performance of political fictions that promote peace and welfare rather than violence and poverty"--